P446 Long-term Clinical Effectiveness And Stoma Outcome Of Fecal Diversion In Refractory Crohn's Proctitis. (21st January 2022) - Benammi, S; Perry, W R; Calini, G; Abdalla, S; Shawki, S F; Larson, D W; Mathis, K L
Abstract: Background: Proctectomy is often recommended when Crohn's proctitis becomes refractory to medical therapy. However, some surgeons offer a temporary diverting stoma in an effort to avoid a permanent stoma. The long-term efficacy of this approach is not well-established. Our aim was to determine the long-term effectiveness of fecal diversion in patients with refractory Crohn's proctitis. Methods: This retrospective study included all patients with Crohn's proctitis who underwent formation of a diverting ileostomy or colostomy for refractory disease from, 1998 to, 2019 in Mayo Clinic Rochester MN. Outcomes were disease recurrence, rate of stoma closure, and proctectomy. Univariate comparisons among categorical variables were performed with Pearson's Chi-square and continuous variables using the student t-test. The cumulative probability of stoma closure was performed with a Kaplan Meier log-rank analysis. Multivariable analysis of risk factors for proctectomy and permanent stoma was achieved with logistic regression. Results: Ninety-seven patients (55.7% female) were included. Ileostomy was the most common stoma type (88.7%, n=86), and colostomy was (11.3%, n=11) (Table.1). Median follow-up was, 4 years (range, 0–14). Active Crohn's at follow-up was reported in, 68.1%. Only, 41.2% of patients underwent attempt at stoma reversal, and, 42.3% required a proctectomy (median, 19.5 months after diversion). At last follow-up, 29.9% were stoma-free, 42.3% had a new permanent stoma, and, 27.8% had the original diverting stoma (Fig.1). The multivariable predictors of proctectomy and permanent stoma were the recurrence of active CD after diversion and the need for other CD-related surgery following stoma creation (Table.2). The limitations of the study are its small sample size and its retrospective nature. The cumulative probability of stoma closure was performed with a Kaplan Meier log-rank analysis (Fig.2). Conclusion: Diversion is effective at alleviating symptoms of Crohn's proctitis in selected patients but does not significantly change disease outcome. Only a small number can avoid a long-term stoma.